NotI passporting to identify species composition of complex microbial systems - Zabarovska, Veronika (Oxford University Press, 2003)
We describe here a new method for large-scale scanning of microbial genomes on a quantitative and qualitative basis. To achieve this aim we propose to create NotI passports: databases containing NotI tags. We demonstrated that these tags comprising 19 bp of sequence information could be successfully generated using DNA isolated from intestinal or fecal samples. Such NotI passports allow the discrimination between closely related bacterial species and even strains. This procedure for generating restriction site tagged sequences (RSTS) is called passporting and can be adapted to any other rare cutting restriction enzyme. A comparison of 1312 tags from available sequenced Escherichia coli genomes, generated with the NotI, PmeI and SbfI restriction enzymes, revealed only 219 tags that were not unique. None of these tags matched human or rodent sequences. Therefore the approach allows analysis of complex microbial mixtures such as in human gut and identification with high accuracy of a particular bacterial strain on a quantitative and qualitative basis.